1995
DOI: 10.1021/tx00043a021
|View full text |Cite
|
Sign up to set email alerts
|

Miscoding by the Exocyclic and Related DNA Adducts 3,N4-Etheno-2'-deoxycytidine, 3,N4-Ethano-2'-deoxycytidine, and 3-(2-Hydroxyethyl)-2'-deoxyuridine

Abstract: 3,N4-Etheno-2'-deoxycytidine, 3-(hydroxyethyl)-2'-deoxyuridine, and 3,N4-ethano-2'-deoxy-cytidine are found in DNA of cells treated with either vinyl chloride or 1,3-bis(2-chloroethyl)-nitrosourea. These exocyclic and related DNA adducts were incorporated into oligodeoxynucleotides, which were then used as templates for primer extension in reactions catalyzed by the Klenow fragment of Escherichia coli DNA polymerase I. The miscoding potential of each lesion was determined quantitatively. DNA primers were readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…In addition, the base pairing preferences are similar for both the 8-HM-εC and εC-containing oligonucleotides. The latter compound is closely related structurally to 8-HM-εC and it has been established that it is a mutagenic lesion (24)(25)(26)(27)(28)(29). Moreover, by molecular modeling, we showed that little difference exists in the planarity and sugar conformations of the two derivatives in duplex DNA.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, the base pairing preferences are similar for both the 8-HM-εC and εC-containing oligonucleotides. The latter compound is closely related structurally to 8-HM-εC and it has been established that it is a mutagenic lesion (24)(25)(26)(27)(28)(29). Moreover, by molecular modeling, we showed that little difference exists in the planarity and sugar conformations of the two derivatives in duplex DNA.…”
Section: Introductionmentioning
confidence: 67%
“…The methyl carbon of the 8-HM-εC remained in the same plane with the exocyclic ring, and hydroxyl group was displaced by only 15° from the exocyclic ring plane. As proposed earlier by Zhang et al (27), the planar conformation of an adduct, such as εC, should aid the stacking interaction of this base during DNA synthesis. Similarly, the planar structure of 8-HM-εC should also contribute to the stacking interaction of this adduct during synthesis.…”
Section: Molecular Modelingmentioning
confidence: 79%
“…In the case of C there is a high frequency of pairing with A or T in vitro, in both transcription (8) and replication (10,17,18). The work of Singer and Spengler (10), Zhang et al (17), and Shibutani et al (18) all agree that there is little or no C⅐C or C⅐G pairing that occurs.…”
Section: Discussionmentioning
confidence: 99%
“…These adducts became of major interest when they were found to be formed by a variety of environmental agents, as well as produced endogenously (3-7). Mutagenesis studies have shown a wide range of mutagenic frequency depending on the type of the adduct, type of mutation and the system used for detection and quantitation (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).For more than one decade, this laboratory has focused on studies on the repair (20-26) and replication͞transcription (8-12) of etheno derivatives of dA, dC, and dG. The differing structures of the etheno adducts and their effect on base pairing and base stacking (27-31) influences both repair and replication.…”
mentioning
confidence: 99%
See 1 more Smart Citation